Agro-Industrial Wastes as Potential Substrates for Rhamnolipid Production by Pseudomonas aeruginosa USM-AR2 - Mohd Shafiq Nasir; Ahmad Ramli Mohd Yahya; Nur Asshifa Md Noh (Tropical Life Sciences Research, 2024)
Rhamnolipid has gained much attention in various fields owing to its distinctive functional properties compared to conventional chemical surfactants, which are mostly derived from petroleum feedstock. Production cost is one of the main challenges in rhamnolipid production, particularly when using refined substrates. One possible solution is to use agro-industrial wastes as substrates for rhamnolipid production. This is a promising strategy due to their abundance and commercially low value, while simultaneously alleviating an agro-industrial waste management problem in the environment. This study aims to evaluate agro-industrial wastes from local crops as possible low-cost alternative substrates for rhamnolipid production by a local isolate, Pseudomonas aeruginosa USMAR2. Various liquid wastes, namely sugarcane molasses, rice washing water, overly mature coconut (OMC) water, empty fruit bunch (EFB) steam effluent, palm sludge oil (PSO) and palm oil mill effluent (POME) were screened as the main carbon source supplementing mineral salt medium (MSM) in the fermentation of P. aeruginosa USM-AR2. Batch fermentation was carried out in a shake flask system, agitated at 200 rpm and incubated at room temperature, 27 ± 2°C for 120 h. Among the substrates tested, PSO exhibited the highest biomass at 20.78 g/L and rhamnolipid production at 1.07 g/L. This study has shown the potential of agro-industrial wastes in Malaysia as an alternative resource for rhamnolipid production, transforming them into value added products, while reducing the amount of wastes discharged into the environment.